New Orleans and the Texas Revolution - Miller, Edward L. (Book collections on Project MUSE., 2004)
"One of the least known but most important battles of the Texas Revolution occurred not with arms but with words, not in Texas but in New Orleans. In the fall of 1835, Creole mercantile houses backed the opposition forces against Santa Anna. As a result, New Orleans capital, some $250,000 in loans, and New Orleans men and arms - two companies known as the New Orleans Greys - went to support the upstart Texans in their battle for independence."